Peran Media Sosial Dalam Peningkatan Partisipasi Pemilih Pemula Pilkada 2024 Di Kecamatan Galesong Kabupaten Takalar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
This study aims to determine the role of social media in increasing the participation of first-time voters in the 2024 regional elections in Galesong District, Takalar Regency. The research method used was a qualitative case study approach. Data were collected through observation, interviews, and documentation. Data analysis was conducted using thematic analysis techniques. The results indicate that social media plays a strategic and significant role in encouraging first-time voter participation. First, from a social contact perspective, social media has proven successful in creating a dynamic interaction space, both directly and indirectly, between first-time voters and fellow voters and election organizers. Second, social media communication serves as a highly effective means of conveying election information. The Takalar Regency General Elections Commission (KPU) successfully utilized digital platforms to disseminate informative and engaging content, enabling first-time voters to quickly and accurately access candidate data, programs, and election schedules. Third, awareness of the role of social media plays a role in increasing first-time voters' understanding of their rights and responsibilities in the democratic process.